Crystalline 6N-grade ultra-pure quartz sand
By purifying quartz ore by hydrothermal temperature difference method and combining sand making and multiple calcining steps, crystalline 6N grade ultra-high-purity quartz sand was successfully prepared, solving the problem of preparation of medium and high purity quartz sand in the existing technology, achieving high purity and high performance quartz sand production.
Patent Information
- Application Number
- CN202411670587.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult to prepare high-purity crystalline 6N grade ultra-high purity quartz sand in the prior art, especially in the application of semiconductor-grade crucible inner layer sand, and traditional methods cannot meet the increasing purity requirements.
The domestic quartz ore is purified in one time by the hydrothermal temperature difference method, and artificial synthetic quartz crystals above level 5N8 are obtained as raw materials for sand making. After sand making and multiple water quenching, pickling, oxygen-energizing and microwave calcining, etc. Finally, crystalline 6N grade ultra-high-purity quartz sand was obtained.
The 6N purity level with a conventional fifteen impurity element content of less than 1 ppm and a hydroxyl content of less than 10 ppm has been achieved, breaking the current status of crystal sand in the field of 6N quartz sand, with higher high-temperature viscosity and crystallization resistance, and can Replace imported amorphous ultra-high-purity quartz sand.
Smart Images

Figure CN119461801A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quartz sand preparation, and in particular relates to crystalline 6N grade ultra-high purity quartz sand used in the fields of semiconductors, optical fibers, etc. Background Art
[0002] Semiconductor-grade quartz sand is an ultra-high purity quartz sand material. It is the raw material for high-end semiconductor devices such as the inner layer of quartz crucibles for silicon wafer growth, photomask substrates, high-end quartz devices in wafer manufacturing processes, and high-temperature containers of various quartz glasses. Within the above applicable scope, the use environment of the inner layer of the quartz crucible is the most stringent. Semiconductor quartz crucibles are mainly used to grow single crystal silicon. Their operating temperature is above 1400°C, and the inner layer of the quartz crucible is in direct contact with silicon liquid. It needs to have high temperature resistance, good thermal stability, and high high temperature viscosity. Factors that affect the stability of semiconductor quartz crucibles include the number of bubbles, impurity content, and hydroxyl content. Therefore, compared with other fields, semiconductor quartz crucibles have extremely high requirements for the purity and particle size of quartz sand.
[0003] The quality requirements of 6N grade ultra-high purity quartz sand in application are as follows: first, it needs to have ultra-low content of impurity elements, requiring the sum of the contents of the 15 conventional impurity elements to be less than 1 ppm; second, there should be few gas and liquid inclusions; third, the hydroxyl content in the quartz sand should be low, so that the semiconductor quartz crucible has higher high-temperature viscosity and anti-crystallization properties.
[0004] At present, ultra-high purity quartz sand has been suppressed by the technology of developed countries such as the United States and Japan. Traditional crystalline quartz sand is purified and processed from natural quartz ore. The highest purity product IOTA-8 produced by Unimin in the United States can only reach the 5N2 level, and there are gas-liquid inclusions, which cannot meet the growing requirements of downstream processes (such as semiconductors). With the development of semiconductor process level, the requirements for the purity of quartz sand are getting higher and higher. The technical route of purifying natural sand cannot meet the requirements of ultra-low impurities in the inner layer of semiconductor-grade crucible sand. After 2000, artificial synthesis methods (such as silicone method) can be used to prepare quartz sand with higher purity. For example, Mitsubishi Chemical in Japan can use silicone synthesis to prepare electronic-grade ultra-high purity quartz sand with a purity of more than 6N, becoming the mainstream product of semiconductor-grade crucible inner layer sand. However, the quartz sand synthesized by this route is amorphous (load softening point is about 1000℃, true density is 2.21 g / m 3 ), has no fixed melting point, and is not as adaptable to crucibles as crystalline quartz sand. In addition, the quartz sand synthesized by this route has a high hydroxyl content (generally around 36 ppm), and its mechanical strength during use and processing is not as good as that of crystalline sand. Summary of the invention
[0005] In order to overcome the above-mentioned technical defects, the present invention provides a crystalline 6N grade ultra-high purity quartz sand, which realizes a primary purification of domestic quartz ore through a hydrothermal temperature difference method. The hydrothermal temperature difference method has low requirements on ore quality for crystallization and impurity removal, and domestic ore sources can meet the requirements. After purification, artificial synthetic quartz crystals of grade 5N8 or above can be obtained as raw materials for sand making; after secondary purification in the sand making link, crystalline 6N grade ultra-high purity quartz sand can be finally obtained. The sum of the fifteen conventional impurity elements of the crystalline 6N grade ultra-high purity quartz sand is less than 1 ppm, and the bubble level, hydroxyl content and other indicators are better than those of amorphous products of the same level, which is of great significance for import substitution and solving the "bottleneck" problem of high-end quartz materials.
[0006] The present invention is specifically implemented by the following technical scheme: according to a crystalline 6N grade ultra-high purity quartz sand proposed by the present invention, the sum of the contents of the conventional fifteen impurity elements is less than or equal to 1 ppm, and the hydroxyl content is less than 10 ppm, and the conventional fifteen impurity elements include Al, Fe, Li, Mn, Cr, Ni, Cu, Mg, Ca, B, K, Na, Ti, Zn and P. The purity of the crystalline 6N grade ultra-high purity quartz sand reaches 6N grade and above, which is much higher than the purity of IOTA-8 in the United States, breaking the previous situation that there was no crystalline sand in the field of 6N grade quartz sand.
[0007] Furthermore, the contents of the fifteen conventional impurity elements are: Al<0.3 ppm, Na<0.05ppm, K<0.01 ppm, Li<0.05ppm, Fe<0.05 ppm, Mn<0.01 ppm, Cr<0.01 ppm, Ni<0.01 ppm, Cu<0.01 ppm, Mg<0.01 ppm, Ca<0.05 ppm, B<0.01 ppm, Ti<0.01 ppm, Zn<0.01 ppm, P<0.01 ppm.
[0008] Alternatively, the contents of the fifteen conventional impurity elements are: Al<0.49 ppm, Na<0.11 ppm, K<0.02 ppm, Li<0.11 ppm, Fe<0.08 ppm, Mn<0.01 ppm, Cr<0.01 ppm, Ni<0.02 ppm, Cu<0.01 ppm, Mg<0.02 ppm, Ca<0.05 ppm, B<0.01 ppm, Ti<0.03 ppm, Zn<0.01 ppm, P<0.01 ppm.
[0009] The aforementioned crystalline 6N grade ultra-high purity quartz sand has a melting point of 1713°C and a density of 2.65 g / m 3 .
[0010] After the aforementioned crystalline 6N grade ultra-high purity quartz sand is melted into a quartz crucible, the inner wall of the quartz crucible is smooth and has no scratches, one bubble of 0.5 mm, and no black spots. The crucible does not deform or bulge during use, and the inner wall of the crucible is smooth after use.
[0011] The aforementioned crystalline 6N grade ultra-high purity quartz sand is prepared according to the following method: (1) placing an artificial synthetic quartz crystal with a purity of 5N8 or above in a quartz tube rotary heating furnace at 480-580°C for 0.5-20 h, with the temperature difference in the furnace precisely controlled at ±0.5°C, and then slowly cooling the temperature; when the temperature drops below 400°C, water quenching is performed, and after the water quenching is completed, the crystal is naturally dried to obtain a quartz crystal block; (2) Secondary water quenching: The dried quartz crystal block in step (1) is placed in a quartz tube rotary heating furnace at a temperature of 450-1150°C, kept warm for 0.5-1h, and then subjected to secondary water quenching with pure water. After the secondary water quenching, the block is naturally dried to obtain a quartz crystal. (3) Sand making: crushing the quartz crystals obtained in step (2) into particles with a particle size of less than or equal to 3 mm by a hammer crusher, and then using a double roller and a sieving method in sequence to obtain quartz sand with a mesh size of 50 to 250 meshes; (4) Ultrasonic screening: the quartz sand obtained in step (3) is screened using an ultrasonic vibrating screen and then dried; (5) Magnetic separation: using a magnetic separator to magnetically separate the quartz sand dried in step (4) to remove magnetic impurities; (6) pickling: pickling the quartz sand obtained in step (5) with a mixed acid solution of any two or three of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid, and after pickling, rinsing the quartz sand with deionized water until it is neutral, and then drying the quartz sand; (7) Calcination with oxygen: the quartz sand dried in step (6) is placed in a quartz tube rotary heating furnace and kept at 300-1000°C for 2 h under air or oxygen conditions. During the calcination process, the air or oxygen supply flow rate is controlled to be 100-2000 mL / h; (8) Microwave calcination: The quartz sand treated in step (7) is sent to a microwave calcination furnace for heating and calcination. During the calcination, gas A and gas B are introduced. Gas A is at least one of hydrogen chloride, hydrogen fluoride, and chlorine. Gas B is at least one of oxygen and nitrogen. The calcination temperature is controlled at 1000-1400°C. The quartz sand enters the calcination furnace from the front end and exits from the rear end. The calcination time is 40-120 min. After the calcination is completed, vacuum is drawn and the calcination temperature and gas flow are maintained to finally obtain crystalline 6N grade ultra-high purity quartz sand.
[0012] Furthermore, in step (1), the cooling rate is 0.3-5°C / min, the particle size of the obtained quartz crystal block is within 8 cm, and the particle size of the quartz crystal obtained in step (2) is within 5 mm.
[0013] Furthermore, in step (5), the magnetic field intensity during magnetic separation is 20,000 Gauss, and the magnetic separation time is 1 hour.
[0014] Furthermore, in step (6), the pickling temperature is controlled at 25-150° C., and the pickling is carried out in a sealed reactor.
[0015] Furthermore, in step (8), the volume proportion of gas A is at least 70%, and the gas flow rates of gas A and gas B are 100-2000 mL / h.
[0016] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages: (1) The total content of the conventional fifteen impurity elements (Al, Fe, Li, Mn, Cr, Ni, Cu, Mg, Ca, B, K, Na, Ti, Zn and P) of the crystalline 6N grade ultra-high purity quartz sand provided by the present invention is less than or equal to 1 ppm, and the hydroxyl content is less than 10 ppm. The purity reaches 6N grade or above, which is much higher than the purity of the US IOTA-8 product (5N2 grade).
[0017] (2) Compared with the existing 6N grade ultra-high purity quartz sand (which is amorphous, with a load softening point of about 1000°C and a true density of 2.21 g / m 3 , no fixed melting point), the 6N grade ultra-high purity quartz sand of the present invention is crystalline, has a fixed melting point, the melting point is 1713°C, and the density is 2.65g / m 3 , low hydroxyl content, the inner wall of the melted quartz crucible is smooth, without scratches, black spots, or gas-liquid inclusions. The crucible does not deform or bulge during use. The inner wall of the crucible is smooth after use, and it can replace imported amorphous ultra-high purity quartz sand.
[0018] (3) Compared with the amorphous quartz sand of the same grade on the market, the crystalline 6N grade ultra-high purity quartz sand of the present invention also has the following characteristics: (a) Strong anti-pollution performance. The silicon and oxygen atoms in the crystalline structure of the 6N grade ultra-high purity quartz sand of the present invention are highly ordered, and the physical and chemical properties are more stable. (b) No gas or liquid inclusions. (c) Low hydroxyl content. The hydroxyl content of the crystalline 6N grade ultra-high purity quartz sand of the present invention can be controlled within 10 ppm. The low hydroxyl content can provide higher high-temperature viscosity for quartz crucibles and higher light transmittance for optical fiber products. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a picture observed under a microscope after the 1# crystalline 6N grade ultra-high purity quartz sand prepared in Example 1 was melted into a quartz crucible. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The present invention is described in detail with specific examples below. If the specific conditions are not specified in the following examples, they are all carried out according to conventional conditions or the conditions recommended by the manufacturer. The raw materials and reagents used without indicating the manufacturer are all conventional products that can be purchased commercially. The present invention proposes a crystalline 6N grade ultra-high purity quartz sand, the total content of the conventional fifteen impurity elements (Al, Fe, Li, Mn, Cr, Ni, Cu, Mg, Ca, B, K, Na, Ti, Zn, P) is ≤1 ppm, the hydroxyl content is less than 10 ppm, the purity reaches 6N grade and above, which is much higher than the 5N2 grade quartz sand of IOTA-8 in the United States. Among them, the contents of the fifteen conventional impurity elements are: Al < 0.3ppm, Na < 0.05ppm, K < 0.01ppm, Li < 0.05ppm, Fe < 0.05ppm, Mn < 0.01ppm, Cr < 0.01ppm, Ni < 0.01ppm, Cu < 0.01ppm, Mg < 0.01ppm, Ca < 0.05ppm, B < 0.01ppm, Ti < 0.01ppm, Zn < 0.01ppm, P < 0.01ppm; or Al < 0.49ppm, Na < 0.11ppm, K < 0.02ppm, Li < 0.11ppm, Fe < 0.08ppm, Mn < 0.01ppm, Cr < 0.01ppm, Ni < 0.02ppm, Cu < 0.01ppm, Mg < 0.02ppm, Ca < 0.05ppm, B < 0.01ppm, Ti < 0.01ppm, Zn < 0.01ppm, P < 0.01ppm. ppm, B<0.01 ppm, Ti<0.03 ppm, Zn<0.01ppm, P<0.01 ppm.
[0024] The aforementioned crystalline 6N grade ultra-high purity quartz sand has a melting point of 1713°C and a density of 2.65 g / m 3 .
[0025] The present invention also provides a method for preparing the above-mentioned crystalline 6N grade ultra-high purity quartz sand, which comprises the following steps: (1) preparing seed crystals; preparing seed crystals by seed crystal cutting and seed crystal etching. This step can be completed by existing methods, for example, the seed crystals can be prepared by the technology disclosed in patent CN115573025A, which will not be described in detail in the present invention.
[0026] (2) Sorting: Domestic quartz ore is used to sort natural quartz, and the sorting conditions are set to SiO 2 The content is ≥99.2%, the total content of metal impurities is ≤80 ppm, of which the Al content is ≤30ppm, the Fe content is ≤15 ppm, and the Ca content is ≤18ppm. The selected natural quartz particle size is 2~4 cm, and its appearance is free of rust, mineral skin, oil stains, and obvious pollution.
[0027] (3) Preparation of artificial synthetic quartz crystals: Add a mineralizer mainly composed of sodium hydroxide into the reactor (for example, the mineralizer can be 0.8 mol / L NaOH solution, 0.4 mol / L Na 2 CO 3 Solution, 0.05 mol / L NaNO 3 The invention discloses a method for preparing an artificial synthetic quartz sand by using a mixture of a 0.05 mol / L LiOH solution and a 240-400 mm diameter autoclave with a pressure of 130-150 MPa. The natural quartz is dissolved and recrystallized in the autoclave under high temperature and high pressure conditions. The autoclave is hoisted into the autoclave pit, and a double baffle is used to control the temperature difference between the dissolution zone and the crystallization zone to be 40°C. The opening rate of the baffle is set to 4%-8%, so that the dissolved natural quartz can convect normally in the dissolution zone and the crystallization zone. The dissolved natural quartz convects into the crystallization zone to form a supersaturated solution, which is crystallized on the seed crystal. The quartz crystal grows stably in the autoclave pit for 120-200 days to obtain an artificial synthetic quartz crystal for preparing crystalline 6N grade ultra-high purity quartz sand. The purity of the obtained artificial synthetic quartz crystal reaches above 5N8 level, without gas-liquid inclusions, and the hydroxyl content is less than 10 ppm.
[0028] (4) The synthetic quartz crystal with a purity of 5N8 or above obtained in step (3) is placed in a quartz tube rotary heating furnace at 480-580°C and kept warm for 0.5-20 hours. The temperature difference in the furnace is precisely controlled at ±0.5°C, and then the temperature is slowly cooled at a rate of 0.3-5°C / min. When the temperature drops below 400°C, a water quenching is performed. After the water quenching is completed, the crystal is naturally dried. The particle size of the quartz crystal block after the water quenching and drying is within 8 cm.
[0029] In this step, high temperature (480~580℃) induces changes in the bond length of silicon-oxygen bonds in the silicon oxide lattice (the bond length becomes longer), which increases the unit cell volume, is beneficial to the exposure of metal element impurities, and is beneficial to the subsequent impurity removal; the purpose of slow cooling is to fully adjust the unit cell structure and fully expose the metal element impurities.
[0030] (5) Secondary water quenching: The quartz crystal block dried in step (4) is placed in a quartz tube rotary heating furnace at a temperature of 450-1150°C for 30 minutes, and then subjected to secondary water quenching with pure water. The secondary water quenching further exposes the impurities, and the block is naturally dried after the secondary water quenching. The particle size of the quartz crystal after the secondary water quenching and drying is within 5 mm. This step can be repeated twice or more to obtain a quartz crystal with a particle size within 5 mm.
[0031] (6) Sand making: The quartz crystals obtained in step (5) are crushed into particles with a particle size of less than or equal to 3 mm by a hammer crusher, and then a double roller and a sieving method are used in sequence to obtain quartz sand with a mesh size of 50 to 250 meshes.
[0032] (7) Screening with an ultrasonic vibrating screen: The quartz sand obtained in step (6) is screened with an ultrasonic vibrating screen at an ultrasonic power of 0.5 kW, and then placed in a quartz tube rotary heating furnace for drying at 300°C-1000°C for a drying time of 0.5 h.
[0033] (8) Magnetic separation: The quartz sand dried in step (7) is subjected to magnetic separation by a magnetic separator; magnetic impurities are removed by magnetic separation, the magnetic field intensity during magnetic separation is 20,000 gauss, and the magnetic separation time is 1 hour.
[0034] (9) Pickling: The quartz sand obtained in step (8) is pickled with a mixed acid solution of any two or three of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid. The pickling temperature is controlled at 25-150°C (in a sealed reactor). After the pickling, the quartz sand is rinsed with deionized water until it is neutral. Then, the quartz sand is placed in a quartz tube rotary heating furnace and dried at 300-1000°C. The drying time can be 0.5 h.
[0035] (10) Calcination with oxygen: The quartz sand dried in step (9) is placed in a quartz tube rotary heating furnace and kept at 300-1000°C for 2 h under air or oxygen conditions. The use of a quartz tube is beneficial to prevent the introduction of new impurities that contaminate the quartz sand during the calcination process. During the calcination process, the air or oxygen supply flow rate is controlled to be 100-2000 mL / h, and the impurity elements in the quartz sand are oxidized by oxygen to achieve the purpose of impurity removal.
[0036] (11) Microwave calcination: The quartz sand treated in step (10) is sent to a microwave calcination furnace for heating and calcination. Microwave heating is more uniform and the heating speed is faster. During microwave calcination, gas A and gas B are introduced. Gas A is at least one of hydrogen chloride, hydrogen fluoride, and chlorine. Gas B is at least one of oxygen and nitrogen. The volume proportion of gas A is at least 70%. The gas flow rate of gas A and gas B is 100-2000 mL / h. The calcination temperature is controlled at 1000-1400°C. The quartz sand enters from the front end of the calcination furnace and exits from the back end. The calcination time is 40-120 min. After the calcination is completed, vacuum is drawn for 40-120 min and the calcination temperature and gas flow are maintained. Finally, crystalline 6N grade ultra-high purity quartz sand is obtained.
[0037] In this step, high temperature can achieve the purpose of dehydration and dehydroxylation, and the different expansion coefficients of impurity elements at high temperature are used to further crack the internal structure of quartz sand to expose the impurity elements; in addition, gases such as hydrogen chloride and hydrogen fluoride can react with metal oxides to form halides. After subsequent vacuuming, the boiling point of the halides of the impurity elements is reduced, and they become gaseous and are taken away by the vacuum system, thereby achieving the purpose of deep purification and impurity removal.
[0038] The total content of the fifteen conventional impurities (A1, Fe, Li, Mn, Cr, Ni, Cu, Mg, Ca, B, K, Na, Ti, Zn, and P) in the crystalline 6N grade ultra-high purity quartz sand prepared by the above method is ≤1 ppm, and the hydroxyl content is less than 10 ppm, which solves the industry difficulty that the current crystalline quartz sand cannot reach the 6N grade.
[0039] Example 1 In step (3), the pressure in the reactor is 130 MPa, the aperture ratio of the baffle is set to 5%, and the quartz crystal grows stably in the reactor pit for 130 days to obtain 1# artificial synthetic quartz crystal for preparing crystalline 6N grade ultra-high purity quartz sand; In step (4), the heating furnace temperature is set to 570°C, and the cooling rate is 2°C / min; In step (5), the temperature of the quartz tube rotary heating furnace is set to 550°C; In step (9), the pickling temperature is set to 60°C; The temperature of oxygen calcination in step (10) is 400°C; The temperature of microwave calcination in step (11) is 1100°C; The remaining operation process is the same as the above-mentioned detailed preparation method, and finally 1# crystalline 6N grade ultra-high purity quartz sand is obtained.
[0040] Example 2 In step (3), the pressure in the reactor is 150 MPa, the aperture ratio of the baffle is set to 8%, and the quartz crystal grows stably in the reactor pit for 180 days to obtain 2# artificial synthetic quartz crystal for preparing crystalline 6N grade ultra-high purity quartz sand; In step (4), the heating furnace temperature is set to 580°C, and the cooling rate is 4°C / min; In step (5), the temperature of the quartz tube rotary heating furnace is set to 750°C; In step (9), the pickling temperature is set to 80°C; The temperature of oxygen calcination in step (10) is 550°C; The temperature of microwave calcination in step (11) is 1050°C; The remaining operation process is the same as the aforementioned detailed preparation method, and finally 2# crystalline 6N grade ultra-high purity quartz sand is obtained.
[0041] The elemental analysis of 1# and 2# artificial synthetic quartz crystals and 1# and 2# crystalline 6N grade ultra-high purity quartz sand was carried out by inductively coupled plasma mass spectrometer ICP-MS. After 1# and 2# artificial synthetic quartz crystals and 1# and 2# crystalline 6N grade ultra-high purity quartz sand were melted into quartz glass by plasma deposition process, their hydroxyl content was detected by Fourier transform infrared spectrometer. The results are shown in Table 1 below.
[0042] Table 1. Element analysis results of artificially synthesized quartz crystals and crystalline 6N grade ultra-high purity quartz sand in Examples 1-2 As shown in Table 1, the total content of the conventional fifteen impurity elements (Al, Fe, Li, Mn, Cr, Ni, Cu, Mg, Ca, B, K, Na, Ti, Zn and P) of the crystalline 6N grade ultra-high purity quartz sand synthesized by the present invention is less than or equal to 1 ppm, the hydroxyl content is less than 10 ppm, and the purity reaches 6N grade and above, which is much higher than the purity of the US IOTA-8 product (5N2 grade). According to the test, the melting point of the 6N grade ultra-high purity quartz sand of the present invention is 1713°C and the density is 2.65g / m 3 , which is crystalline 6N grade ultra-high purity quartz sand.
[0043] The crystalline 6N grade ultra-high purity quartz sand prepared in Example 1 was melted into a quartz crucible. The inner wall of the crucible was smooth, without scratches or black spots. The results were as follows when observed under a polarizing microscope: Figure 1As shown, it can be seen that within the observation area, the bubble content at a depth of 0.1 mm is 13, the bubble content at a depth of 0.5 mm is 7, the bubble content at a depth of 1 mm is 9, and the bubble content at a depth of 1.5 mm is 6, indicating that the quality of the crystalline 6N grade ultra-high purity quartz sand of the present invention meets the normal use standard and is superior to the quartz sand imported from the United States. The crucible was subjected to a crystal pulling experiment, and no abnormal phenomena such as deformation and bulging occurred during use, and the inner wall of the crucible was smooth after use.
[0044] The application of the crystalline 6N grade ultra-high purity quartz sand of the present invention is not limited to the semiconductor-grade quartz crucible described above, but can also be applied to the fields of optical fiber, special glass, high-end quartz devices, etc.
[0045] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A crystalline 6N grade ultra-high purity quartz sand, characterized in that The total content of the fifteen conventional impurity elements is less than or equal to 1 ppm, and the hydroxyl content is less than 10 ppm. The fifteen conventional impurity elements include Al, Fe, Li, Mn, Cr, Ni, Cu, Mg, Ca, B, K, Na, Ti, Zn and P.
2. The crystalline 6N grade ultra-high purity quartz sand according to claim 1, characterized in that The contents of the fifteen conventional impurity elements are: Al<0.3 ppm, Na<0.05 ppm, K<0.01 ppm, Li<0.05 ppm, Fe<0.05ppm, Mn<0.01 ppm, Cr<0.01 ppm, Ni<0.01 ppm, Cu<0.01 ppm, Mg<0.01 ppm, Ca<0.05ppm, B<0.01 ppm, Ti<0.01 ppm, Zn<0.01 ppm, P<0.01 ppm.
3. The crystalline 6N grade ultra-high purity quartz sand according to claim 1, characterized in that The contents of the fifteen conventional impurity elements are: Al<0.49 ppm, Na<0.11 ppm, K<0.02 ppm, Li<0.11 ppm, Fe<0.08ppm, Mn<0.01 ppm, Cr<0.01 ppm, Ni<0.02 ppm, Cu<0.01 ppm, Mg<0.02 ppm, Ca<0.05ppm, B<0.01 ppm, Ti<0.03 ppm, Zn<0.01 ppm, P<0.01 ppm.
4. The crystalline 6N grade ultra-high purity quartz sand according to claim 1, characterized in that Its melting point is 1713℃ and its density is 2.65 g / m 3 .
5. The crystalline 6N grade ultra-high purity quartz sand according to claim 1, characterized in that Prepare as follows: (1) Place the artificial synthetic quartz crystal with a purity of 5N8 or above in a heating furnace at 480-580°C for 0.5-20 hours, and precisely control the temperature difference in the furnace within ±0.5°C, and then control the temperature to slowly cool down; when the temperature drops below 400°C, perform a water quenching and rapid cooling, and then naturally dry it after the water quenching and rapid cooling to obtain a quartz crystal block; (2) Secondary water quenching: The dried quartz crystal block in step (1) is placed in a quartz tube rotary heating furnace at a temperature of 450-1150°C, kept warm for 0.5-1h, and then subjected to secondary water quenching with pure water. After the secondary water quenching, the block is naturally dried to obtain a quartz crystal. (3) Sand making: crushing the quartz crystals obtained in step (2) into particles with a particle size of less than or equal to 3 mm by a hammer crusher, and then using a double roller and a sieving method in sequence to obtain quartz sand with a mesh size of 50 to 250 meshes; (4) Ultrasonic screening: the quartz sand obtained in step (3) is screened using an ultrasonic vibrating screen and then dried; (5) Magnetic separation: using a magnetic separator to magnetically separate the quartz sand dried in step (4) to remove magnetic impurities; (6) pickling: pickling the quartz sand obtained in step (5) with a mixed acid solution of any two or three of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid, and after pickling, rinsing the quartz sand with deionized water until it is neutral, and then drying the quartz sand; (7) Calcination with oxygen: the quartz sand dried in step (6) is placed in a quartz tube rotary heating furnace and kept at 300-1000°C for 2 h under air or oxygen conditions. During the calcination process, the air or oxygen supply gas flow rate is controlled to be 100-2000 mL / h; (8) Microwave calcination: The quartz sand treated in step (7) is sent to a microwave calcination furnace for heating and calcination. During the calcination, gas A and gas B are introduced. Gas A is at least one of hydrogen chloride, hydrogen fluoride, and chlorine. Gas B is at least one of oxygen and nitrogen. The calcination temperature is controlled at 1000-1400°C. The quartz sand enters the calcination furnace from the front end and exits from the rear end. The calcination time is 40-120 min. After the calcination is completed, vacuum is drawn and the calcination temperature and gas flow are maintained to finally obtain crystalline 6N grade ultra-high purity quartz sand.
6. The crystalline 6N grade ultra-high purity quartz sand according to claim 5, characterized in that The cooling rate in step (1) is 0.3-5°C / min, the particle size of the obtained quartz crystal block is within 8 cm, and the particle size of the quartz crystal obtained in step (2) is within 5 mm.
7. The crystalline 6N grade ultra-high purity quartz sand according to claim 5, characterized in that During the magnetic separation in step (5), the magnetic field intensity is 20,000 Gauss and the magnetic separation time is 1 hour.
8. The crystalline 6N grade ultra-high purity quartz sand according to claim 5, characterized in that In step (6), the pickling temperature is controlled at 25-150° C., and the pickling is carried out in a sealed reactor.
9. The crystalline 6N grade ultra-high purity quartz sand according to claim 5, characterized in that In step (8), the volume proportion of gas A is at least 70%, and the gas flow rates of gas A and gas B are 100-2000 mL / h.